Improving Precision in Posterior Composite Restorations with the Innovative Stamp Technique: A Case Report - Gupta, Swati Rani; Joshi, Reema; Thapa, Asha; Shrestha, Reetu (Journal of College of Medical Sciences-Nepal, 2025)
Background Posterior composite restorations, using the traditional methods, can often be technique-sensitive and may not always result in an exact replication of the tooth's natural anatomy and occlusion. The “Stamp technique” has emerged as a reliable method for producing biomimetic posterior restorations with accurate occlusal topography, requiring little or no occlusal adjustment. By creating preoperative impression of the tooth’s occlusal surface before cavity preparation, this technique allows for precise reproduction of natural occlusal morphology, thereby reducing chair time and enhancing esthetic outcomes. This case report highlights the application of the occlusal stamp technique in a patient requiring multiple posterior composite restorations.